Upaya Hukum Peninjauan Kembali Terhadap Putusan Bebas - Hapit Suhandi (JOURNAL of LEGAL RESEARCH, 2020)
AbstractThis legal research aims to determine the reasons for the convicted perpetrators of criminal acts in filing legal remedies for judicial review in an acquittal. The rules regarding the reasons for filing a judicial review are contained in Article 263 of the Criminal Procedure Code. The main requirement for filing legal remedies for judicial review is in Article 263 paragraph (1), namely that the court's decision must be legally binding. Then Article 263 paragraph (2) explains the material reasons for filing a legal reconsideration effort. The reason the convicted person filed a judicial review is in accordance with the provisions of Article 263 paragraph (2) letter c, the Cassation decision clearly shows a judge's mistake or an obvious mistake. The review is carried out by the prosecutor / public prosecutor as a legal breakthrough in an effort to obtain justice and truth due to new circumstances (novum), or mistakes or mistakes of judges and / or decisions that contradict one another. The Attorney General / Public Prosecutor does not use the cassation for the sake of the law which is his right and prefers to file a review. The Indonesian State Government System, as contained in the explanation of the 1945 Constitution of Indonesia is a state based on law (Rechtsstaat), not based on mere power (Machtsstaa). In this study using qualitative research methods, with a normative juridical approach. The results of this study, the study used normative legal research in which data collection was carried out through literature study and interviews with several sources, which were then analyzed qualitatively. The results of this study conclude that the prosecutor / public prosecutor filed a review on the legal basis of the provisions of Article 263 paragraph (3) of the Criminal Procedure Code, the provisions of Article 68 paragraph (1) of Law Number 3 of 2009 and the provisions of Article 24 paragraph (1) of Law No. 48 of 2009. Keywords: Reconsideration, Free Decision, Legal Remedies